Digital Marketing Communication And Consumer Purchase Behaviour: With Reference To Home Appliance Market (Journal of Namibian Studies : History Politics Culture, 2023)
Digital marketing or online marketing, is the promotion of brands to connect with potential customers, applying the internet and other forms of digital communication. This includes email, social media, web-based advertising and text and multimedia messages as a marketing channel. Digital marketing communication which is the communication through digital or electronic media among businesses and consumers has grown rapidly during the COVID-19 era and post COVID-19 era. Consumer Purchase Behaviour in Home Appliance Market is affected by Digital Marketing Communication. This paper reflects digital marketing communication and consumer purchase behaviour in home appliance market.